Distal Placement of an End-to-Side Bypass Graft Anastomosis: A 3D Computational Study. (13th November 2012) - Di Cicco, John; Demuren, Ayodeji
Abstract : A three-dimensional (3D) computational fluid dynamics study of shear rates around distal end-to-side anastomoses has been conducted. Three 51% and three 75% cross-sectional area-reduced 6 mm cylinders were modeled each with a bypass cylinder attached at a 30-degree angle at different placements distal to the constriction. Steady, incompressible, Newtonian blood flow was assumed, and the full Reynolds-averaged Navier-Stokes equations, turbulent kinetic energy, and specific dissipation rate equations were solved on a locally structured multiblock mesh with hexahedral elements. Consequently, distal placement of an end-to-side bypass graft anastomosis was found to have an influence on the shear rate magnitudes. For the 75% constriction, closer placements produced lower shear rates near the anastomosis. Hence, there is potential for new plaque formation and graft failure.